Crenças e práticas docentes quanto à promoção e prevenção em saúde na educação infantil, em Santarém-Pará - SALGADO, Andréa Leite de Alencar (Universidade Federal do Oeste do Pará, 2021)
Health promotion and prevention within the school is part of a comprehensive and multidisciplinary vision of the human being, considering people in their family, community, social and environmental context, still being a newly inserted theme in the National Curriculum References and requires implementation in institutions’ daily practice. In early childhood education, health promotion and prevention may be or may not be present in actions of caring and education in everyday child care, being carried out or not by teachers of the same. In this sense, starting from the theoretical assumption that teachers’ beliefs are connected with the practices carried out daily in school context, this study aimed to investigate the teachers’ beliefs and practices on health promotion and prevention in early childhood education, based on accounts of teachers belonging to the Municipal Childhood Education in Santarém, Pará. To achieve these objectives a qualitative research of exploratory means through individual interviews with teachers from 10 Child Education Municipal Units of Santarém was held. The study included 53 teachers, with at least two years of experience, aged 22 to 56 years mostly with training in teaching and pedagogy. Data from the interviews were divided into two thematic corpus and analyzed using the free software IRAMUTEQ. Analysis of both corpus, one of beliefs and other of practices, resulted in 5 classes each. The classes concerning beliefs, brought beliefs about the determinants of the health-disease process, school papers, family and health professionals in prevention and health promotion and beliefs related to prevention and promotion through hygiene practices. Practices classes showed educational promotion and preventive health practices, hygiene practices as a form of health promotion at school, school and family activities to promote health and the description of the daily routine in the nursery. It was noted by the empirical results, the ratio of 3 beliefs classes to 3 practises’ classes. Through these results it was inferred that beliefs are related to practices and those beliefs interfere in the daily practices of these teachers. It is expected that the results contribute both in academic and social environment. Under the academic focus, the study provides an initial survey of data on daily practices in municipal kindergartens, and shows the relationship between beliefs and practices. Under the corporate aegis, the study provides results that may be input to create more effective strategies of promotion and prevention in health in Early Childhood Education. It was concluded to be of great importance to continue studies on the promotion of children's health as a responsibility of educational institutions in partnership with family and health services, and it must be considered the fact that it is impossible to care for and educate children without influencing social practices related to the maintenance and recovery of health and child welfare, or without being influenced by these practices.